INFLUENCE OF D-FRUKTOSA AND EGG YOLK TOWARD PERANAKAN ETAWA (PE) GOAT SPERMATOZOA QUALITY IN SEXING PROCESS USE SENTRIFUGATION GRADIEN DENSITAS PERCOLL METHODE ON TIME BEFORE FREEZING AT 3000 RPM - Oktavianto, Sulis (Jurnal Sains Peternakan, 2014)
This research was done in laboratory Balai Besar Inseminasi Buatan (BBIB) Singosari at 24th September until 30th October 2013. This aim of research intent to know use influence D-Fruktosa and egg yolk toward Peranakan Etawa (PE) goat spermatozoa quality in sexing process use sentrifugation gradient densitas percoll method on time Before Freezing at 3000 rpm. That method used is laboratory research with Completely Randomized Design (CRD) from 4 treatment and every treatment from 3 repetation. This research indicate that spermatozoa X (P>0.05) at using D-Fruktosa and yolk towards motilitas, viabilitas and abnormalitas. While spermatozoa Y toward the real influence (P<0.05) on using D. Fruktosa and yolk towards motility, viability, and abnormality.Keywords : Before Freezing, Egg yolk, Spermatozoa Quality, Sexing process